Fenomena Career Decision Regret pada Mahasiswa Perantau: Analisis Faktor Internal, Eksternal, dan Kontekstual - Nengsih Nengsih; M Ramli; Diniy Hidayatur Rahman; Yuliati Hotifah (JKI (Jurnal Konseling Indonesia), 2026)
This study aimed to (1) identify the level of career decision regret, (2) examine the internal, external, and contextual factors contributing to its development, and (3) develop an empirically grounded integrative model of career decision regret among migrant students. A mixed-method approach with an explanatory sequential design was employed. The quantitative phase involved 86 migrant undergraduate students selected through purposive sampling, followed by in-depth interviews with 17 participants who reported moderate to high levels of career decision regret. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through thematic analysis. The findings revealed that 71% of respondents experienced moderate to high levels of career decision regret (M = 3.42, SD = 0.68, α = 0.82). Thematic analysis identified five major themes: identity misalignment, inauthentic decision-making, expectation–reality discrepancy, social comparison and counterfactual thinking, and the psychological vulnerability of migrant students. These findings extend the theoretical understanding of career decision regret and provide evidence for strengthening career guidance and counseling services for migrant students